Uso y selección de microhábitat en un ensamble de anuros del Chaco Serrano de Argentina - Nieva Cocilio, Rodrigo A. (Universidad de Costa Rica, 2020)
Introduction: Research on spatial resource usage and partition strategies is important to understand the mechanisms of coexistence in sympatric amphibian species, even more when there are temporal variations in habitat availability. Objective: To learn about the patterns of microhabitat use, its seasonal variations and the possible influence of phylogeny on an anuran assembly of the Chaco Serrano in Argentina. Methods: Samplings were carried out in the Valle Fértil Natural Park protected area, Valle Fértil Department, San Juan, between 2012 and 2017. In the field, we recorded the microhabitat where each specimen was found, and we also measured site variables. In addition, microhabitats availability was determined. Data were analyzed using Manly’s selectivity index. Generalized linear models (GLM) were used to assess temporal variations in microhabitat use. Results: The species evaluated were: Rhinella arenarum arenarum, Leptodactylus latrans, Pleurodema tucumanum and Odontophrynus occidentalis. All species showed differences in usage frequencies: R. a. arenarum showed preferences for rocky and aquatic sites, P. tucumanum showed preferences towards bare soil and rocky sites, L. latrans and O. occidentalis showed greater preferences for rocky and aquatic sites. All species but Odontophrynus exhibited seasonal variations in microhabitat selection and usage. Odontophrynus occidentalis showed differences in usage proportions among microhabitats. Conclusions: This study shows plasticity in microhabitat usage as an important determinant of anuran spatial distribution, without apparent restrictions imposed by space competition or phylogeny. When species activity is coincident, the space resource may be distributed in a way that species overlap is reduced.